(untitled) (Proceedings of International Conference on Special Education, 2015)
Emergent literacy research demonstrates that children’s oral language, reading, and writing develop concomitantly in literate environment in early family settings (Razfar & Gutierrez, 2003). To become a skilled reader, children need a rich language and conceptual knowledge base, a broad and deep vocabulary, and verbal reasoning abilities to understand messages that are conveyed through print (McCardle & Chhabra, 2004; McCardle, Scarborough, & Catts, 2001). This qualitative case study research explored how literacy development in early years was enhanced in a print-rich multilingual environment through a language-rich home and school collaboration program provided by an inclusive school. Participants were five children, enrolled in an age-appropriate inclusive preschool program, from five families in a multilingual setting including preschool educators and caregivers. Specifically, this study sought to answer: (1) What strategies were utilized by both the school and the families to create meaningful language –rich home and school program to children (children with and without disabilities)? (2) How did parents in language-rich home-link program perceive their child’s home to be a “Real Book” environment? (3) How did parents realize language-rich home and school program to be a crucial goal in their child’s literacy development during preschool years? ; and (4) How did parents and professionals involved define and support language-rich home and school program? Data collection focused on emergent literacy of young children and how home environment and family practice supported such development utilizing triangulation of semi-structured interviews; field observations of authentic interfaces during parents’ education program meetings and workshops; on-site examination of literate environment; focus-group discussion, document and videotape analysis. Results revealed evocative discernments gained from young children’s early literacy development that challenges preschool educators to reflect more essentially and inclusively about home-school collaboration and parental involvement in early literacy development.